Antibacterial and Antitubercular Activity of Novel Benzothiazole-Aryl Amine Derivatives Tethered through Acetamide Functionality - Hakim, Farhana; Roshan Salfidoer, S. (Asian Journal of Chemistry, 2021)
A novel series of substituted benzothiazole-N-phenyl acetamides were synthesized through a feasible scheme and characterized by IR, 1H NMR and mass spectral methods. All the synthesized compounds were screened for antibacterial activity against two, Gram-positive strains: Staphylococcus aureus, Bacillus subtilis; four, Gram-negative strains: Escherichia coli, Salmonella typhi, Pseudomonas aeruginosa and Klebsiella pneumonia; and antitubercular activity against mycobacterial strain: Mycobacterium tuberculosis. Among the 15 compounds (6a-o) tested, three compounds 6e, 6l and 6m have demonstrated high potency with MIC values ranges from 6.25-12.5 μg/mL against both Gram-positive and Gram-negative strains. Compounds 6e and 6l displayed remarkable antitubercular activity with MIC value of 25 μg/mL.